Strategies of the Department of Transportation in Regulating Street-Side Parking in Binjai City - Br Sembiring, Yuninta Sartika; Rangkuti, Zoraya Alfathin (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The primary goal of this research is to explore the Department of Transportation's approach to managing public roadside parking in Binjai City, as well as the challenges it faces. This is due to the role of the Binjai City Transportation Service as a key provider of services to the residents of Binjai City. According to the Minister for Administrative Reform's Decree No. 25 of 2004, public services encompass all activities carried out by service providers to meet the needs of service recipients and comply with legal requirements. The regulations governing public roadside parking in Binjai City are outlined in Mayor of Binjai Regulation No. 27 of 2018, which amends the retribution rates for parking services on public roads as specified in Regional Regulations of Binjai City No. 4 of 2011 regarding Public Service Retribution. The research approach employed is descriptive with a focus on qualitative analysis. Data collection involved interviews, observations, and documentation review. The data was qualitatively analysed using a theoretical framework centred on persuasive communication between the Department of Transportation and individuals engaged in illegal parking, as proposed by Effendy. The results of this study indicate that the persuasive communication pattern used by the Department of Transportation is weak against illegal parking actors. It is hoped that socialization will be further enhanced in the form of a persuasive approach itself, namely by inviting illegal parking actors to want to be sheltered or fostered by the Department of Transportation.